How the environment shapes the plastisphere of microplastic in a coastal lagoon – a living lab test - Jake Bowley; Ashley G. Bell; Craig Baker-Austin; Stephen Michell; Ceri Lewis (Marine Pollution Bulletin, 2026)

Species differences in glycerol-3-phosphate metabolism reveals trade-offs between metabolic adaptations and cell proliferation - Kateryna Gaertner; Mügen Terzioglu; Craig Michell; Riikka Tapanainen; Jaakko Pohjoismäki; Eric Dufour; Sina Saari (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2025)

Global mesozooplankton communities show lower connectivity in deep oceanic layers - Oriol Canals; Jon Corell; Ernesto Villarino; Guillem Chust; Eva Aylagas; Iñaki Mendibil; Craig T. Michell; Juan Ignacio González‐Gordillo; Xabier Irigoien; Naiara Rodríguez‐Ezpeleta (Molecular Ecology, 2024)
Mesozooplankton is a key component of the ocean, regulating global processes such as the carbon pump, and ensuring energy transfer from lower to higher trophic levels. Yet, knowledge on mesozooplankton diversity, distribution and connectivity at global scale is still fragmented. To fill this gap, we applied DNA metabarcoding to mesozooplankton samples collected during the Malaspina‐2010 circumnavigation expedition across the Atlantic, Indian and Pacific oceans from the surface to bathypelagic depths. We highlight the still scarce knowledge on global mesozooplankton diversity and identify the Indian Ocean and the deep sea as the oceanic regions with the highest proportion of hidden diversity. We report no consistent alpha‐diversity patterns for mesozooplankton at a global scale, neither across vertical nor horizontal gradients. However, beta‐diversity analysis suggests horizontal and vertical structuring of mesozooplankton communities mostly attributed to turnover and reveals an increase in mesozooplankton beta‐diversity with depth, indicating reduced connectivity at deeper layers. Additionally, we identify a water mass type‐mediated structuring of mesozooplankton bathypelagic communities instead of an oceanic basin‐mediated as observed at upper layers. This suggests limited dispersal at deep ocean layers, most likely due to weaker currents and lower mixing of water mass types, thus reinforcing the importance of oceanic currents and barriers to dispersal in shaping global plankton communities.

Molecular phenotyping uncovers differences in basic housekeeping functions among closely related species of hares ( Lepus spp., Lagomorpha: Leporidae) - Kateryna Gaertner; Craig Michell; Riikka Tapanainen; Steffi Goffart; Sina Saari; Manu Soininmäki; Eric Dufour; Jaakko L. O. Pohjoismäki (Molecular Ecology, 2023)
Speciation is a fundamental evolutionary process, which results in genetic differentiation of populations and manifests as discrete morphological, physiological and behavioural differences. Each species has travelled its own evolutionary trajectory, influenced by random drift and driven by various types of natural selection, making the association of genetic differences between the species with the phenotypic differences extremely complex to dissect. In the present study, we have used an in vitro model to analyse in depth the genetic and gene regulation differences between fibroblasts of two closely related mammals, the arctic/subarctic mountain hare ( Lepus timidus Linnaeus) and the temperate steppe‐climate adapted brown hare ( Lepus europaeus Pallas). We discovered the existence of a species‐specific expression pattern of 1623 genes, manifesting in differences in cell growth, cell cycle control, respiration, and metabolism. Interspecific differences in the housekeeping functions of fibroblast cells suggest that speciation acts on fundamental cellular processes, even in these two interfertile species. Our results help to understand the molecular constituents of a species difference on a cellular level, which could contribute to the maintenance of the species boundary.

Genomic evidence for contrasting patterns of host‐associated genetic differentiation across shared host‐plant species in leaf‐ and bud‐galling sawflies - Craig T. Michell; Natascha Wagner; Marko Mutanen; Kyung Min Lee; Tommi Nyman (Molecular Ecology, 2023)
Resource specialization and ecological speciation arising through host‐associated genetic differentiation (HAD) are frequently invoked as an explanation for the high diversity of plant‐feeding insects and other organisms with a parasitic lifestyle. While genetic studies have demonstrated numerous examples of HAD in insect herbivores, the rarity of comparative studies means that we still lack an understanding of how deterministic HAD is, and whether patterns of host shifts can be predicted over evolutionary timescales. We applied genome‐wide single nucleotide polymorphism and mitochondrial DNA sequence data obtained through genome resequencing to define species limits and to compare host‐plant use in population samples of leaf‐ and bud‐galling sawflies (Hymenoptera: Tenthredinidae: Nematinae) collected from seven shared willow (Salicaceae: Salix ) host species. To infer the repeatability of long‐term cophylogenetic patterns, we also contrasted the phylogenies of the two galler groups with each other as well as with the phylogeny of their Salix hosts estimated based on RADseq data. We found clear evidence for host specialization and HAD in both of the focal galler groups, but also that leaf gallers are more specialized to single host species compared with most bud gallers. In contrast to bud gallers, leaf gallers also exhibited statistically significant cophylogenetic signal with their Salix hosts. The observed discordant patterns of resource specialization and host shifts in two related galler groups that have radiated in parallel across a shared resource base indicate a lack of evolutionary repeatability in the focal system, and suggest that short‐ and long‐term host use and ecological diversification in plant‐feeding insects are dominated by stochasticity and/or lineage‐specific effects.

Finding flies in the mushroom soup: Host specificity of fungus‐associated communities revisited with a novel molecular method - Janne Koskinen; Tomas Roslin; Tommi Nyman; Nerea Abrego; Craig Michell; Eero J. Vesterinen (Molecular Ecology, 2019)
Fruiting bodies of fungi constitute an important resource for thousands of other taxa. The structure of these diverse assemblages has traditionally been studied with labour‐intensive methods involving cultivation and morphology‐based species identification, to which molecular information might offer convenient complements. To overcome challenges in DNA extraction and PCR associated with the complex chemical properties of fruiting bodies, we developed a pipeline applicable for extracting amplifiable total DNA from soft fungal samples of any size. Our protocol purifies DNA in two sequential steps: (a) initial salt–isopropanol extraction of all nucleic acids in the sample is followed by (b) an extra clean‐up step using solid‐phase reversible immobilization ( SPRI ) magnetic beads. The protocol proved highly efficient, with practically all of our samples—regardless of biomass or other properties—being successfully PCR ‐amplified using metabarcoding primers and subsequently sequenced. As a proof of concept, we apply our methods to address a topical ecological question: is host specificity a major characteristic of fungus‐associated communities, that is, do different fungus species harbour different communities of associated organisms? Based on an analysis of 312 fungal fruiting bodies representing 10 species in five genera from three orders, we show that molecular methods are suitable for studying this rich natural microcosm. Comparing to previous knowledge based on rearing and morphology‐based identifications, we find a species‐rich assemblage characterized by a low degree of host specialization. Our method opens up new horizons for molecular analyses of fungus‐associated interaction webs and communities. Fruiting bodies of fungi constitute an important resource for thousands of other taxa. The structure of these diverse assemblages has traditionally been studied with labour‐intensive methods involving cultivation and morphology‐based species identification, to which molecular information might offer convenient complements. To overcome challenges in DNA extraction and PCR associated with the complex chemical properties of fruiting bodies, we developed a pipeline applicable for extracting amplifiable total DNA from soft fungal samples of any size. Our protocol purifies DNA in two sequential steps: (a) initial salt–isopropanol extraction of all nucleic acids in the sample is followed by (b) an extra clean‐up step using solid‐phase reversible immobilization ( SPRI ) magnetic beads. The protocol proved highly efficient, with practically all of our samples—regardless of biomass or other properties—being successfully PCR ‐amplified using metabarcoding primers and subsequently sequenced. As a proof of concept, we apply our methods to address a topical ecological question: is host specificity a major characteristic of fungus‐associated communities, that is, do different fungus species harbour different communities of associated organisms? Based on an analysis of 312 fungal fruiting bodies representing 10 species in five genera from three orders, we show that molecular methods are suitable for studying this rich natural microcosm. Comparing to previous knowledge based on rearing and morphology‐based identifications, we find a species‐rich assemblage characterized by a low degree of host specialization. Our method opens up new horizons for molecular analyses of fungus‐associated interaction webs and communities.

Evidence for mi RNA ‐mediated modulation of the host transcriptome in cnidarian–dinoflagellate symbiosis - Sebastian Baumgarten; Maha J. Cziesielski; Ludivine Thomas; Craig T. Michell; Lisl Y. Esherick; John R. Pringle; Manuel Aranda; Christian R. Voolstra (Molecular Ecology, 2018)
Reef‐building corals and other cnidarians living in symbiotic relationships with intracellular, photosynthetic dinoflagellates in the genus Symbiodinium undergo transcriptomic changes during infection with the algae and maintenance of the endosymbiont population. However, the precise regulatory mechanisms modulating the host transcriptome are unknown. Here, we report apparent post‐transcriptional gene regulation by mi RNA s in the sea anemone Aiptasia , a model system for cnidarian–dinoflagellate endosymbiosis. Aiptasia encodes mainly species‐specific mi RNA s, and there appears to have been recent differentiation within the Aiptasia genome of mi RNA s that are commonly conserved among anthozoan cnidarians. Analysis of mi RNA expression showed that both conserved and species‐specific mi RNA s are differentially expressed in response to endosymbiont infection. Using cross‐linking immunoprecipitation of Argonaute, the central protein of the mi RNA ‐induced silencing complex, we identified mi RNA binding sites on a transcriptome‐wide scale and found that the targets of the mi RNA s regulated in response to symbiosis include genes previously implicated in biological processes related to Symbiodinium infection. Our study shows that cnidarian mi RNA s recognize their mRNA targets via high‐complementarity target binding and suggests that mi RNA ‐mediated modulations of genes and pathways are important during the onset and maintenance of cnidarian–dinoflagellate endosymbiosis.

Evaluation of the global marine mesozooplankton diversity using alternative metabarcoding approaches - Corell Jon; Aylagas Eva; Michell Craig; González-Gordillo J.Ignacio; Irigoien Xabier; Rodriguez-Ezpeleta Naiara (Frontiers in Marine Science, 2016)

Metatranscriptome analysis of the reef-building coral Orbicella faveolata indicates holobiont response to coral disease - Camille A. Daniels; Sebastian Baumgarten; Lauren K. Yum; Craig T. Michell; Till Bayer; Chatchanit Arif; Cornelia Roder; Ernesto Weil; Christian R. Voolstra (Frontiers in Marine Science, 2015)